Fulfillment of Sleep Needs in Elderly Insomnia in South Sibolga District, Sibolga City - Anggi Hanafiah Syanif; Joni Haryanto; Elida Ulfiana (Journal Of Nursing Practice, 2022)
Background: Insomnia is one of the most common sleep problems in older adults (elderly). Insomnia in the elderly is caused by several factors, namely health status factors, drug use, environmental conditions, psychological stress, diet/nutrition. Purpose: overcoming insomnia in the elderly by combining two theories, namely Comfort and Environmental. Methods: The type of research used in this study is qualitative with a phenomenological approach. the number of participants who participated in this study were fifteen people. Collecting data using Focus Group Discuss (FGD), Observation, and in-depth interviews, the results of data collection in this study using analysis techniques Triangulation method (Focus Group Discuss, in-depth interviews, and observation). Results: This study produced five main themes, namely: 1) physical, 2) psychology, 3) religion, 4) social, 5) environment. Conclusion: In achieving the quality and quantity of sleep for the elderly who experience insomnia, it is expected that the elderly can fulfill their comfort and cleanliness in their surrounding environment.